Helping with Homework? Homework as a Site of Tension for Parents and Teenagers - Solomon, Yvette; Warin, Jo; Lewis, Charlie (British Educational Research Journal, 2002)
The setting of homework is strongly encouraged by the Department for Education and Employment on the assumption that support from parents, once gained, is unproblematic and useful. However, a number of researchers have observed the possibility of a negative impact of homework on families. This article presents interview data from families with teenagers, in which homework was described as a significant site of parent-teenager tensions. For many parents, homework was invested with the opportunity for reparation for their own scholastic failures or lost opportunities. Others felt that they lacked the competence to help and were disenfranchised by homework demands. Parents' concerns about their children's futures create a climate of pressure to succeed as they support a homework agenda that is not necessarily their own and which they have little power to influence.